Adolescent lumbar disc herniation: a case report - King, Laurie (1996)
Lumbar spine disc herniations in children are a relatively rare condition reported to occur in less than 3% of those presenting with low back pain. Unlike the adult, the etiology and clinical picture often provides few clues to making the diagnosis. Although conservative management is the treatment of choice, surgical intervention may be required in some cases. The role of spinal manipulation in these cases may be of limited value. A case report is presented that illustrates the difficulty in making the diagnosis and conservatively managing lumbar disc herniations in children.